2013
DOI: 10.4172/2155-9872.1000169
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Soluble Oligomers Formed by PB1-F2 Influenza A Virus Protein in vitro

Abstract: PB1-F2 is a short polypeptide of approximately 90 amino acids which is dispensable for the viral replication [1]. PB1-F2 is not encoded by all human and swine IAV strains although nearly all the avian IAV express a full length version of the protein suggesting a host-specific function. It is tempting to correlate the mortality rate of a particular viral strain and the expression of PB1-F2 since contemporary H1N1 strains like the pandemic H1N1/2009 virus that no longer express PB1-F2 appeared to be less virulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…6, A and B). We previously showed that PB1-F2 converts into amyloid-like structures in the presence of a diluted anionic detergent SDS (concentration of SDS below its CMC of 0.23% (w/v)) (27,29,34). The long PB1-F2 fibrils obtained were of micron sizes and showed no significant cytotoxic effect on A549 cells (Fig.…”
Section: Secondary Structure Of Pb1-f2 In a Membranementioning
confidence: 84%
See 1 more Smart Citation
“…6, A and B). We previously showed that PB1-F2 converts into amyloid-like structures in the presence of a diluted anionic detergent SDS (concentration of SDS below its CMC of 0.23% (w/v)) (27,29,34). The long PB1-F2 fibrils obtained were of micron sizes and showed no significant cytotoxic effect on A549 cells (Fig.…”
Section: Secondary Structure Of Pb1-f2 In a Membranementioning
confidence: 84%
“…Spectroscopic analyses revealed the presence of ␣-helical structures within PB1-F2 only in the concentrated TFE solution, which is far from physiological conditions. In the membrane mimic environment, PB1-F2 was demonstrated to aggregate to amyloid-like structures with a characteristic amyloidal cross-␤-sheet secondary structure (27)(28)(29). Additionally, PB1-F2 can adopt ␤-sheet conformation and oligomerize to amyloid structures within infected cells, as shown for IAV-infected monocytes and epithelial cells (27,28).…”
mentioning
confidence: 92%
“…XXXX, XXX, XXX−XXX C Biosensing Recombinant PB1-F2 in Monomeric and Oligomeric States. Two antibodies were used to detect PB1-F2: mAb R14, which specifically recognizes the monomeric random coiled form of PB1-F2,6,20 and pAb A11, a conformational antibody raised against a generic conformational β-sheet epitope present in amyloid oligomers 1,22. The elaboration of an…”
mentioning
confidence: 99%
“…Full length PB1-F2(1-90) converts from random into amyloid-like structures in a diluted solution of anionic detergent SDS (concentration of SDS below its CMC of 0.23 %w/v) [13,15,17]. To determine if PB1-F2 (1-52) and PB1-F2 (53-90) also convert into amyloid-like structures, the proteins were dissolved in 10 mM sodium-acetate buffer, pH 5 containing 0.05 %v/w SDS.…”
Section: Resultsmentioning
confidence: 99%